Cooling, Cryopreservation and Gene Expression in Mammalian Cells - Fuller, B.; Green, C.; Grischenko, V. I. (Problems of Cryobiology and Cryomedicine, 2004)
Altered gene expression in response to cooling has been identified in many prokaryotic organisms, plants and lower invertebrates such as insects, but the effects in mammalian cells are less clearly understood. This review was undertaken to identify responses of mammalian cells to cold temperatures, such as might be encountered in therapeutic procedures where body temperatures are lowered, in preservation of cells and organs, and in cryopreservation. In general, cold elicits a range of stress responses through identified signaling pathways, which may determine the survival or otherwise of the cells. Under conditions of mild hypothermia, there is evidence for responses which reflect an ordered acclimation to the new environment, whilst deep cooling invokes a more general stress response. The concepts reported here form part of a presentation to the Society for Low Temperature Biology (2002, London) Meeting Chromosomes, Genes and Cryobiology